Influence of B2O3 doping on synthesis of MgTiO3 ceramics from recycled magnesia-hercynite materials. (15th December 2021) - Jia, Xiaodong; Mao, Shuo; Tian, Lin; Chen, Shujiang; Li, Guohua; Gao, Wei
Abstract: Herein, magnesium metatitanate (MgTiO3 ) ceramics were synthesised using recycled magnesia-hercynite (MH) bricks as the raw materials to achieve solid waste reusing of cement kiln refractories. The recycled MH materials were mixed with anatase TiO2 to investigate the effect of addition of doped B2 O3 during the synthesis of MgTiO3 ceramics at 1400 °C. Phase compositions and microstructural studies were performed using x-ray diffraction (XRD) and scanning electron microscope (SEM), respectively. In addition, energy-dispersive spectroscopy (EDS) was conducted and the dielectric properties of the samples were studied. Results show that the addition of B2 O3 can promote sintering, improve shrinkage, promote densification, stabilise MgTiO3 lattice, and inhibit the formation of MgTiO3 . In addition, the presence of appropriate amount of B2 O3 can accelerate the material diffusion and result in grain growth through the formation of intercrystalline liquid phase. Results also suggest that an increase in dielectric constant results in a decrease in dielectric loss. It was concluded that 2 wt% was the optimum amount of B2 O3 required to obtain the most favourable synthesis rate of MgTiO3 (98.2%). The samples exhibited a maximum density of 3.69 g·cm −3 and excellent microwave dielectric properties at ε r  = 18.28 and tan δ  = 0.086.